Stop doing people's homework for them, they won't learn anything.
2006-12-19 11:25:54
·
answer #1
·
answered by mojo2093@sbcglobal.net 5
·
0⤊
0⤋
5 times 6 equals 30/ 2 times 4 equals 8/ 30 minus 8 equals 22!
2006-12-19 11:24:01
·
answer #2
·
answered by no.#1 Mom 4
·
0⤊
0⤋
6
2006-12-19 11:25:02
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
4 and -1
2006-12-19 11:21:16
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
4 and -1
2006-12-19 11:20:56
·
answer #5
·
answered by jaffarkelshac 3
·
0⤊
0⤋
5X - 2Y = 22
X + Y = 3 => Y = 3 - X sub into first equation
5X - 2(3 - X) = 22
5X + 2X - 6 = 22
7X = 22 + 6 = 28
X = 28/7 = 4
Y = 3 - 4 = -1
2006-12-19 11:22:49
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
5x - 2y = 22
x + y = 3
7x = 22 + 6 = 28
x = 4
y = 3 - x = 3 - 4 = -1
So
x = 4
y = -1
2006-12-19 11:31:13
·
answer #7
·
answered by Northstar 7
·
0⤊
0⤋
OK!
5*X - 2*Y = 22
X + Y = 3
5*X - 2*Y = 22
2*X + 2*Y = 2*3
Add the equations to get:
7*X= 28
X=4
X+Y=3, so, 4 +Y=3 ==> Y=-1
DONE!
2006-12-19 11:18:23
·
answer #8
·
answered by Jerry P 6
·
0⤊
1⤋
Okay, so...
5x-2y=22
x+y=3
Now we start changing stuff around.
5x-2y=22
-2x+-2y=-6
5x-2y=-2x-2y+28
7x=28
x=4
5*4=20
22-20=2
2/-2=1
y=-1
The numbers are 4 and -1.
2006-12-19 11:21:15
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
5a - 2b = 22
(a + b = 3) -----> multiply this by 2
----------------
5a - 2b = 22
+ 2a + 2b = 6 ---------> add the top with the bottom
-----------------
7a = 28
a = 4
therefore 4 + b = 3
and b = -1
2006-12-19 11:23:00
·
answer #10
·
answered by frdsgt 2
·
0⤊
0⤋